Power and Religion in Baroque Rome Barberini Cultural Policies - Rietbergen, Peter (Brill's Studies in Intellectual History, 2005)
This study analyzes the ways in which a variety of cultural manifestations were the necessary preconditions for (religious) policy and power in the Rome of Urban VIII (1623-1644). Precisely their interaction created what we now call 'Baroque Culture'.